2010
DOI: 10.1089/end.2009.0597
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Magnetic Resonance Imaging of Prostate Cancer

Abstract: The purpose of this article is to review both routine T2-weighted and new MRI techniques in the imaging of prostate cancer (PCa) for focal therapy. T2-weighted imaging, knowledge of MRI prostate zonal anatomy, cancer morphology, and intraprostatic tumor spread remain essential for clinical PCa imaging; however, new techniques, such as dynamic contrast-enhanced MRI, diffusion-weighted imaging, and magnetic resonance spectroscopic imaging yield significant improvements in identification and volume estimation. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…That approach, which may identify some patients with higher risk disease, has not been embraced by most advocates of active surveillance and does not appear necessary in most patients. Dynamic contrastenhanced (dce) magnetic resonance imaging (mri) is emerging as a means to further assess extent of disease in patients with, for example, borderline psa kinetics and minimal disease on biopsy 20 .…”
Section: Are the Clinical Tools Available To Make Activementioning
confidence: 99%
“…That approach, which may identify some patients with higher risk disease, has not been embraced by most advocates of active surveillance and does not appear necessary in most patients. Dynamic contrastenhanced (dce) magnetic resonance imaging (mri) is emerging as a means to further assess extent of disease in patients with, for example, borderline psa kinetics and minimal disease on biopsy 20 .…”
Section: Are the Clinical Tools Available To Make Activementioning
confidence: 99%
“…To improve prostate cancer detection, conventional T 2 WI is complemented by functional MR techniques such as DCE-MRI, DWI, and MRS. [8][9][10] The present study investigated the use of T 2 WI and DCE-MRI at 3.0T to differentiate cancerous prostate tissue from noncancerous tissue, and found that DCE-MRI was significantly more sensitive, accurate and had better NPV for cancer detection than T 2 WI. Specificity and PPV were not significantly different between DCE-MRI and T 2 WI, however.…”
Section: Discussionmentioning
confidence: 84%
“…6,7 Functional MR techniques (such as dynamic contrast-enhanced MRI [DCE-MRI], diffusion-weighted imaging [DWI], and magnetic resonance spectroscopy [MRS]) have been used to increase the diagnostic accuracy of MR in prostate cancer. [8][9][10] Dynamic contrast-enhanced MRI is useful in imaging tumour vascularization, vascular permeability and perfusion. 11 The method involves intravascular injection of contrast agents and imaging of their concentrations in blood and tissue over time.…”
Section: Introductionmentioning
confidence: 99%
“…24 The low-risk group contained patients with T1-T2a tumor, Gleason score <7, and PSA<10 ng/mL; intermediate-risk…”
Section: Study Design and Patient Populationmentioning
confidence: 99%